Sea urchin mtDBP is a two-faced transcription termination factor with a biased polarity depending on the RNA polymerase - Fernandez-Silva, Patricio (Oxford University Press, 2001)
The sea urchin mitochondrial displacement (D)-loop binding protein mtDBP has been previously identified and cloned. The polypeptide (348 amino acids) displays a significant homology with the human mitochondrial transcription termination factor mTERF. This similarity, and the observation that the 3′ ends of mitochondrial RNAs coded by opposite strands mapped in correspondence of mtDBP-binding sites, suggested that mtDBP could function as transcription termination factor in sea urchin mitochondria. To investigate such a role we tested the capability of mtDBP bound to its target sequence in the main non-coding region to affect RNA elongation by mitochondrial and bacteriophage T3 and T7 RNA polymerases. We show that mtDBP was able to terminate transcription bidirectionally when initiated by human mitochondrial RNA polymerase but only unidirectionally when initiated by T3 or T7 RNA polymerases. Time-course experiments indicated that mtDBP promotes true transcription termination rather than transcription pausing. These results indicate that mtDBP is able to function as a bipolar transcription termination factor in sea urchin mitochondria. The functional significance of such an activity could be linked to the previously proposed dual role of the protein in modulating mitochondrial DNA transcription and replication.